2007
DOI: 10.1038/sj.mt.6300289
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Human Plasma Components and A Xenogenic Adenovirus Vector: Reduced Immunogenicity During Gene Transfer

Abstract: By the time we are adolescents most of us have been in contact with several of the >50 human adenovirus (HAd) serotypes. These common subclinical infections lead to an efficient anti-adenovirus cross-reacting adaptive immunity. During gene therapy, the ubiquitous anti-adenovirus humoral response and complement activation will modify and dictate vector biodistribution, as well as the response to the virion and transgene(s). In this study, we assayed the interactions of a xenogenic adenovirus derived from canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…These technical factors may help to explain why there is considerable disagreement among previous studies on the mechanisms by which Ad5 activates human complement. Although all studies agree that the lectin pathway plays no role, some studies found that only the classical pathway is involved (9,66), other studies found that the alternative but not the classical pathway is involved (4,23), and an additional study found that both the classical and alternative pathways are involved depending on the concentration of Ad (41).…”
Section: Vol 82 2008 Mechanisms For Uptake Of Adenovirus By Kupffermentioning
confidence: 92%
See 1 more Smart Citation
“…These technical factors may help to explain why there is considerable disagreement among previous studies on the mechanisms by which Ad5 activates human complement. Although all studies agree that the lectin pathway plays no role, some studies found that only the classical pathway is involved (9,66), other studies found that the alternative but not the classical pathway is involved (4,23), and an additional study found that both the classical and alternative pathways are involved depending on the concentration of Ad (41).…”
Section: Vol 82 2008 Mechanisms For Uptake Of Adenovirus By Kupffermentioning
confidence: 92%
“…Several previous in vitro studies with human plasma or serum have shown that Ad5 can bind to and activate complement (4,9,23,41). One issue with using human material is that individual humans have variable levels of specific anti-Ad antibodies that activate complement via the classical pathway (9).…”
Section: Resultsmentioning
confidence: 99%
“…We did not include other host blood factors in this study. Among these, there are lactoferrin, ␣-defensin, complement factor C1 and C3, coagulation FVII, and protein C (61,62). Combining these factors in an exclusively human assay will contribute to a better understanding of the host-pathogen interaction with HAds.…”
Section: Discussionmentioning
confidence: 99%
“…The neutralizing activity of the plasma of each volunteer enrolled was determined by transduction inhibition assays using the 911 cell line (28).…”
Section: Methodsmentioning
confidence: 99%
“…It was then relevant to determine whether Ad5-NAb titers correlated with the presence and/or the proliferative capacity of Ad-specific CD4 T cells isolated from gut mucosal tissues in naturally adenovirus-infected volunteers. To address this issue, Ad5-NAb titers were determined for each volunteer as previously described (28). The volunteers were stratified into two groups based on their Ad5 serostatus: (i) Ad5 NAb low (titer, Ͻ18) and (ii) Ad5 NAb high (Ͼ18) (6,20).…”
Section: Vol 85 2011 Dna-c/nyvac-c-induced T-cell Responses In the mentioning
confidence: 99%